Test and Start for People Living With HIV and Who Use Drugs in Low and Middle Income Countries - Thomas F. Kresina; Lisa Kaplowitz; Mitra Ahadpour; Kimberly Johnson (HIV/AIDS Research and Treatment-Open Journal, 2016)
“Test and Start” implements the World Health Organization (WHO) recommendation of “treat all” by providing anti-retroviral treatment to persons newly diagnosed with HIV infection, at the time of their diagnosis. This HIV treatment algorithm is derived from recent international clinical trials and the recent international HIV treatment guidelines by WHO, recommending all people living with HIV be provided anti-retroviral treatment. This “treat all” recommendation removes any and all limitations for receiving anti-retroviral treatment for all people living with HIV, including people who use drugs. However, there are a limited number of “Test and Start” programs that have focused on the barriers to anti-retroviral treatment for people who use drugs. With an increasing number of low and middle income countries developing guidance for “Test and Start” programs, this articles identified four elements that support access to and successful initiation of the early initiation of anti-retroviral treatment for people living with HIV, who use drugs. The elemental services are: outreach with social services, screening for and management of substance use disorders, comprehensive primary care and differentiated care in anti-retroviral treatment. Together these services can provide a supportive foundation for “Test and Start” programs for people living with HIV, who use drugs.